Prevalence of Ectoparasites and Hemoparasites in Rodents and Shrews in Ilemela District, Mwanza Region, Tanzania - Aheir Achuil Deng; Emmanel P. Lita; Erneo Bernardo Ochi; Jahashi Nzalawahe; Abdul A. S. Katakweba (Universitas Airlangga, 2024)
Background: Rodents and shrews play an important role in the transmission and spreading of zoonotic diseases in Tanzania and worldwide. Purpose: This study aims to identify ectoparasites and hemoparasites in rodents and shrews captured in Ilemela District, Mwanza Region, Tanzania. Methods: Rodents and shrews were captured using Sherman live traps and modified wire cages, both of which were placed indoors, peri-domestically, and in agricultural fields. The animals were anaesthetized using diethyl ether, and blood samples were collected aseptically from the heart. Thin and thick smears were prepared for the identification of hemoparasites. Results: The overall prevalence of ectoparasites was 56.4%, with the following ectoparasites identified: Laelaps echininus (39.6%), Polyplax spp. (4.0%), Xenopsylla cheopis (2.7%), and Heamaphysalis leachi (0.7%). The highest prevalence of ectoparasites was observed in Mastomys natalensis. In terms of sex, male animals showed a higher prevalence of ectoparasites (59.0%) than female animals. Additionally, the prevalence of hemoparasites was 35.5%, with the following parasites identified: Anaplasma spp. (18.8%), Trypanosoma lewisi (0.7%), Plasmodium spp. (1.3%), Bipolar coccobacilli (2.7%), and Bacillus spp. (3.4%). Anaplasma spp. was identified in all infested rodent species, with the highest prevalence observed in Mus musculus (34.4%) and Mastomys natalensis (27.3%). However, T. lewisi was only identified in Rattus rattus (0.7%), whereas no hemoparasites was identified in Crocidura spp. Conclusion: This study provides baseline information on the prevalence of ectoparasites and hemoparasites in rodents and shrews in Ilemela district, Mwanza Region, Tanzania. Therefore, monitoring of these parasites is important for preparedness and early warning preparation for the control of rodent-borne diseases.